Long-term fuel retention in JET ITER-like wall. (2nd February 2016) - Heinola, K; Widdowson, A; Likonen, J; Alves, E; Baron-Wiechec, A; Barradas, N; Brezinsek, S; Catarino, N; Coad, P; Koivuranta, S; Krat, S; Matthews, G F; et al.
Abstract: Post-mortem studies with ion beam analysis, thermal desorption, and secondary ion mass spectrometry have been applied for investigating the long-term fuel retention in the JET ITER-like wall components. The retention takes place via implantation and co-deposition, and the highest retention values were found to correlate with the thickness of the deposited impurity layers. From the total amount of retained D fuel over half was detected in the divertor region. The majority of the retained D is on the top surface of the inner divertor, whereas the least retention was measured in the main chamber on the mid-plane of the inner wall limiter. The recessed areas of the inner wall showed significant contribution to the main chamber total retention. Thermal desorption spectroscopy analysis revealed the energetic T from DD reactions being implanted in the divertor. The total T inventory was assessed to be .